Placenta-derived multipotent mesenchymal stromal cells: A promising potential cell-based therapy for canine inflammatory brain disease - Amorim, Rogério Martins [UNESP]; Clark, Kaitlin C.; Walker, Naomi J.; Kumar, Priyadarsini; Herout, Kyle; Borjesson, Dori L.; Wang, Aijun (Springer Nature, 2020)
Background: Canine inflammatory brain disease (IBD) is a severe inflammatory disorder characterized by infiltration of activated immune cell subsets into the brain and spinal cord. Multipotent mesenchymal stromal cells (MSCs) are a promising therapy for IBD, based on their potent pro-angiogenic, neuroprotective, and immunomodulatory properties. The aims of this study were to compare the immunomodulatory attributes of canine adipose-derived MSCs (ASCs) and placenta-derived MSCs (PMSCs) in vitro. These data will serve as potency information to help inform the optimal MSC cell source to treat naturally occurring canine IBD. Methods: Indoleamine 2,3 dioxygenase (IDO) activity and prostaglandin E2 (PGE2) concentration at baseline and after stimulation with interferon gamma (IFNγ) and/or tumor necrosis factor alpha (TNFα) were measured from canine ASC and PMSC cultures. Leukocyte suppression assays (LSAs) were performed to compare the ability of ASCs and PMSCs to inhibit activated peripheral blood mononuclear cell (PBMC) proliferation. IDO activity and PGE2; interleukin (IL)-2, IL-6, and IL-8; TNFα; and vascular endothelial growth factor (VEGF) concentrations were also measured from co-culture supernatants. Cell cycle analysis was performed to determine how ASCs and PMSCs altered lymphocyte proliferation. Results: Activated canine MSCs from both tissue sources secreted high concentrations of IDO and PGE2, after direct stimulation with IFNγand TNFα, or indirect stimulation by activated PBMCs. Both ASCs and PMSCs inhibited activated PBMC proliferation in LSA assays; however, PMSCs inhibited PBMC proliferation significantly more than ASCs. Blocking PGE2 and IDO in LSA assays determined that PGE2 is important only for ASC inhibition of PBMC proliferation. Activated ASCs increased IL-6 and VEGF secretion and decreased TNFα secretion, while activated PMSCs increased IL-6, IL-8, and VEGF secretion. ASCs inhibited lymphocyte proliferation via cell cycle arrest in the G0/G1 and PMSCs inhibited lymphocyte proliferation via induction of lymphocyte apoptosis. Conclusion: Our results demonstrate that ASCs and PMSCs have substantial in vitro potential as a cell-based therapy for IBD; however, PMSCs more potently inhibited lymphocyte proliferation by inducing apoptosis of activated lymphocytes. These data suggest that the mechanism by which ASCs and PMSCs downregulate PBMC proliferation differs. Additional studies may elucidate additional mechanisms by which canine MSCs modulate neuroinflammatory responses.
Keywords: Adipose tissue; Animal model; Canine; Immunomodulation; Inflammatory brain disease; Mesenchymal stromal cell; Multiple sclerosis; Multipotent progenitor cell; Placenta; Translational research